Hadith of Gratitude and Mental Health: A Conceptual Analysis in The Works of Al-Ghazali - Aniqoh Aniqoh; Abdul Mufid; Siti Mujibatun; A. Hasan Asy’ari Ulama’i (Jurnal Ushuluddin, 2025)
This research is This study is motivated by the growing prevalence of mental health problems caused by individuals’ inability to cope with life’s pressures. In this context, the Islamic teaching of gratitude holds significant relevance as a spiritual foundation for maintaining emotional balance. The research aims to contextualize the concept of gratitude derived from the hadiths as understood by Al-Ghazali in Ihya’ Ulumuddin and to examine its relevance to contemporary mental health concepts. The theoretical framework is based on Al-Ghazali’s understanding of gratitude, which consists of three dimensions: knowledge, inner state, and action. Regarding mental health, Al-Ghazali mentions three essential methods of self-development—mujahadah (spiritual struggle), tazkiyatun-nafs (self-purification), and riyadhah (spiritual exercise).This study employs a qualitative approach through library research, utilizing takhrij and dirayah analysis of hadiths related to gratitude found in Al-Ghazali’s works. The analysis is descriptive and analytical, aiming to reveal the conceptual and contextual meanings of gratitude within Al-Ghazali’s intellectual framework. In his view, gratitude is a comprehensive spiritual process that goes beyond verbal expression, requiring the integration of knowledge, inner awareness, and practical deeds as a form of acknowledgment of Allah’s blessings.The findings indicate that Al-Ghazali’s concept of gratitude comprises three main dimensions: knowledge, spiritual state, and practice. These dimensions play a crucial role in developing Islamic mental health by cultivating spiritual awareness, inner peace, and balance between psychological and spiritual aspects. Through tazkiyatun-nafs (self-purification) and riyadhah (spiritual training), individuals are trained to face life’s trials with a positive attitude, avoid despair, and remain conscious that all goodness originates from Allah. Al-Ghazali also asserts that trials are blessings in disguise and should be viewed as opportunities to recognize other forms of divine grace. Thus, his concept of gratitude provides a substantial contribution to the development of an Islamic paradigm of mental health anchored in spiritual and moral values